1982
DOI: 10.5962/bhl.title.60100
|View full text |Cite
|
Sign up to set email alerts
|

Llandoverian graptolites of the northern Canadian Cordillera : Petalograptus, Cephalograptus, Rhaphidograptus, Dimorphograptus, Retiolitidae, and Monograptidae

Abstract: Llandoverian graptolite faunas from 13 major sections in a region extending from the southern Northwest Territories to northern Yukon are divisible into 13 zones, oi v^\\\c\\{\\q persculptus and magnus zones are only tentatively recognized. The biostratigraphic units, from oldest to youngest, are the persculptus Zone?, acuminatus Zone, atavus Zone, acinaces Zone, gregarius Zone, triangulatus Zone, magnus Zone?, argenteus Zone, convolutus Zone, sedgwicki Zone, turriculatus Zone, spiralis Zone, and sakmaricus-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 7 publications
5
45
0
Order By: Relevance
“…Paramonoclimacis sidjachenkoi appears to be restricted to the upper part of the Lituigraptus convolutus Biozone, Llandovery (Melchin ; Russel‐Houston ) in Arctic Canada and Lenz () documented it from this biozone in northern Yukon. There are no reports of this species outside of the Lituigraptus convolutus Biozone.…”
Section: Paramonoclimacis Sidjachenkoi (Obut and Sobolevskaya In Obut Ementioning
confidence: 99%
“…Paramonoclimacis sidjachenkoi appears to be restricted to the upper part of the Lituigraptus convolutus Biozone, Llandovery (Melchin ; Russel‐Houston ) in Arctic Canada and Lenz () documented it from this biozone in northern Yukon. There are no reports of this species outside of the Lituigraptus convolutus Biozone.…”
Section: Paramonoclimacis Sidjachenkoi (Obut and Sobolevskaya In Obut Ementioning
confidence: 99%
“…This genus has been most commonly reported from strata no lower than the S. guerichi or S. turriculatus zones (lower Telychian) (e.g., Bouček and Münch, 1944;Münch, 1952;Schauer, 1971;Hutt, 1974;Bjerreskov, 1975;Rickards, 1976;Chen, 1984;Ge, 1990;Tomczyk et al, 1991;Loydell, 1993;Lenz et al, 2003), although Zalasiewicz et al (2009) recorded a possible occurrence of Pseudoplegmatograpus from the S. sedgwickii Zone in UK (based on Hutt, 1974), and occurrences in the Stimulograptus halli Zone (uppermost Aeronian), continuing into the lower Telychian. In addition, Lenz (1982) reported Pseudoplegmatograptus obesus from the S. sedgwickii Zone in northwestern Canada, as well as a single unillustrated specimen assigned to P. cf. obesus from the L. convolutus Zone.…”
Section: Introductionmentioning
confidence: 99%
“…-Descriptions of chemically isolated material of several Streptograptus and Pseudostreptograptus species were provided by Loydell & Maletz (2004). Other taxa are described in Lenz (1982;S. richardsonensis) and Štorch (1998a; S. pericoi Material.…”
Section: Stimulograptus Sp Figures 19b 21ementioning
confidence: 99%
“…at Pot Burn (Williams et al 2003), the Aeronian/Telychian boundary has been shown to lie within oxic grey mudstones. At Pot Burn, graptolites from the guerichi Biozone occur within a single 10 mm thick hemipelagite layer, the only graptolitic horizon in 9 m of otherwise barren grey mudstones.Of the sections collected by Lenz (1982) in the Northern Canadian Cordillera, the Blackstone River section would seem to have the greatest potential for exposing a continuous section through the Aeronian/Telychian boundary, with the upper Aeronian Cephalograptus extrema present at 77.2 m and a lower Telychian assemblage at 80.2 m. Whether the section is graptolitic through these 3 m is not known. In Arctic Canada Melchin (1989) recorded (at e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation